Outsourcing the border within: private citizens as border guards, state sovereignty, and civil peace - Zedner, L (Oxford University Press, 2022)
The policing of borders is a core state function that cannot be delegated without detriment to its legitimate authority, yet many states not only contract out to private security, but also co-opt private citizens as agents of immigration control. Under the notorious ‘Hostile Environment’ policy, the UK government created a network of citizen border agents by obliging health workers, teachers, employers, landlords, and charitable organisations working with migrants, the poor, and the homeless to check immigration status and report so-called ‘illegals’. This creation of a ‘border within’ disperses controls across the territory of the nation state, and makes private citizens complicit in policing migration. Although the UK government formally ended the Hostile Environment policy in 2017, its successor, the ‘Compliant Environment’, continues to co-opt private citizens as collaborators in immigration control. Legal challenges by civil society organisations and others have questioned whether citizens act as agents of the state or as private actors and, if as agents, on whose authority they police, but they have had limited success in resisting the trend. This chapter explores the origins, aims, and implications for state sovereignty of outsourcing state responsibility to police immigration. It explores the legal and ethical implications of co-opting citizens to argue that it makes police of private citizens and creates suspects not only of non-citizens but of those in minority communities. In so doing, it undermines social trust, civil order, and delegitimises the authority of the sovereign state to police its borders.